METHODOLOGY FOR APPLYING THE “JOURNEY TO THE PAST” TECHNOLOGY IN HISTORICAL LOCAL STUDIES LESSONS - Yuldasheva Nilufar Nazarovna (Modern American Journals, 2025)
This article discusses the essence of organizing non-traditional lessons based on a new modern approach to the study of the history of the region by students in historical local history education, the role of pedagogical technologies in education.
Keywords: new pedagogical technology, non-traditional education, didactic games, problem questions and tasks, skills, abilities, analysis.